Pengaruh Model Problem Based Learning (Pbl) terhadap Kemampuan Memecahkan Masalah dan Hasil Belajar IPA di Smp Negeri 1 Adiluwih - Ratika Novianti (Attractive : Innovative Education Journal, 2024)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on problem-solving ability and science learning outcomes of students at SMP Negeri 1 Adiluwih. This study used an experimental method with a nonequivalent pretest-posttest control group design. The sample of the study was grade VIII students consisting of an experimental class with the application of the PBL model and a control class with conventional learning methods. Data collection techniques were carried out through essay tests to measure problem-solving ability and cognitive learning outcomes. The data obtained were analyzed using normality tests, homogeneity tests, and Analysis of Covariance (ANCOVA) tests to determine the significance of the influence of the learning model. The results showed that the PBL model had a significant effect on problem-solving ability and student learning outcomes. The average posttest score and the difference between the pretest and posttest in the experimental class were higher than the control class. In terms of problem-solving ability, students taught with the PBL model showed significant improvement, as seen from the higher average posttest score and the results of the covariance analysis correction that supported the superiority of the PBL model. Likewise, the cognitive learning outcomes of students in the experimental class showed significant improvement compared to the control class. The conclusion of this study is that the PBL model is effective in improving students' problem-solving skills and science learning outcomes. This model is able to encourage students to think critically, creatively, and actively in the learning process. The results of this study recommend the widespread application of the PBL model to improve the quality of science learning in secondary schools.